LEARNING ENGLISH IN COVID-19 PANDEMIC: A CASE STUDY - Fitria Aftinia (Proceedings of the International Conference on Literacy and Education, 2022)
Abstract This case study aims to know how English learning during Covid-19 pandemic. It is conducted in a private Junior High School in Surabaya. The data were obtained from students’ questionnaire, learning outcomes, and attendance. The result of students’ questionnaire is analyzed and categorized. If the result belongs to good or very good category, it can be considered as positive result. The result of students’ learning outcomes can be considered to be successful if it reaches classical completeness ≥ 80%, while the students’ activity can be seen from their attendance in learning. The findings show that most students give positive result towards online learning. The learning outcomes does not meet the standard – less than 80% of students who reached minimum completeness criteria. The attendance of students is less than 80%. It is suggested to conduct blended learning and use various games to make students excited in learning. Keywords: case study, covid-19 pandemic, learning English